2001
DOI: 10.1007/s001980170083
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density in an Immigrant Population from Southeast Asia

Abstract: The epidemiology of bone loss in populations of Asian heritage is still poorly known. This study compared the skeletal status of a convenience sample of 396 Southeast Asian immigrants (172 Vietnamese, 171 Cambodians and 53 Laotians) residing in Rochester, Minnesota in 1997 with 684 white subjects previously recruited from an age-stratified random sample of community residents. Areal bone mineral density (BMD, g/cm2) and volumetric bone mineral apparent density (BMAD, g/cm3) were determined for lumbar spine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2002
2002
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 41 publications
0
33
1
1
Order By: Relevance
“…The latter observation reinforces the notion that individuals of particular races should not be viewed as members of a uniform class [56] but rather that efforts should be made to explore differences among the component ethnic groups [31]. Unfortunately, no obvious explanation for differences in bone density between Somali and AA women was found with the limited data available here.…”
Section: Discussioncontrasting
confidence: 39%
See 4 more Smart Citations
“…The latter observation reinforces the notion that individuals of particular races should not be viewed as members of a uniform class [56] but rather that efforts should be made to explore differences among the component ethnic groups [31]. Unfortunately, no obvious explanation for differences in bone density between Somali and AA women was found with the limited data available here.…”
Section: Discussioncontrasting
confidence: 39%
“…When bone size was adjusted for, BMAD values at the lumbar spine and femoral neck were actually somewhat greater for Somali than for white women. Likewise, recent studies have shown that adjustment for bone or body size reduces apparent differences in bone density between white and Asian women [31,44,[51][52][53][54][55]. However, this correction did not equilibrate bone density values among those of African heritage, as BMAD values were still significantly greater among AA than Somali women.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations